Community and ecology dynamics of place, sustainability and politics - McCright, Aaron M.; Clark, Terry N. (Amsterdam ; Oxford : Elsevier JAI, 2006)
Humans live in social communities that are embedded ecologically within overlapping biophysical environments. This volume facilitates an ongoing dialogue between community sociologists and environmental sociologists about how humans interact with each other in social communities and with biophysical environments in an ecological community. The chapters in this volume contribute to three related areas of scholarship. First, chapters two through four deal with the ecological and social significance of place. The authors of these three chapters examine different theoretical and substantive dilemmas regarding place and ecology. Their scholarship investigates the significance of place across a range of natural, modified, and built environments. Second, chapters five through seven deal with the challenges of local sustainability. The authors of these three chapters perform scholarship on social, economic and ecological dimensions of local sustainability. Third, chapters eight through eleven deal with local environmental politics. The authors of these four chapters examine the various dynamics of local political processes in communities across three continents. These scholars explicitly examine how the structure of political opportunities in different localities affects the mobilization necessary to recognize and ameliorate environmental problems. We anticipate that this volume furthers the cross-pollination of ideas between community sociologists and environmental sociologists. Ultimately, the heightened and sustained communication between these two groups of scholars may lead to emergent theoretical, methodological, and substantive insights that may contribute to the discipline of sociology more generally. Different sections of the book address ecological and social significance of place, challenges of local sustainability, and local environmental politics. The book enhances the interplay of ideas between community sociologists and environmental sociologists, and stimulates thought that will contribute to the general field of sociology.
The intersection between community sociology and environmental sociology / Aaron M. McCright and Terry Nichols Clark -- Place: where community and environment meet / Aaron T. McCright and Terry Nichols Clark -- Loss, attachment, and place: land loss and community in coastal Louisiana / David Burley, Pam Jenkins and Brian Azcona -- Community by experiment: recursive practice in landscape design and ecological restoration / Matthias Gross -- Visualizing ethnic vernacular landscapes in American cities / Jerome Krase -- Dimensions of local sustainability / Aaron M. McCright and Terry Nichols Clark -- The challenge of disaster reduction / Raymond Murphy -- Sustainable development in the city of Tampere: working together with residents / Ari Ylönen -- The social ecology of health in New York City / Hilary Silver and Peter Messeri -- Political dynamics of local environmental problems / Aaron M. McCright and Terry Nichols Clark -- Explaining the outcomes of campaigns against waste incinerators in England: community, ecology, political opportunities, and policy contexts / Christopher Rootes -- The political opportunity structure of the environmental movement in U.S. communities / Aaron M. McCright and Terry Nichols Clark -- The political ecology of plague in the global network of cities: the SARS epidemic of 2002-2003 / Kent P. Schwirian -- The role of Guanxi in the emerging environmental movement in China / Lei Xie and Arthur P.J. Mol -- The shared future of environmental sociology and community sociology / Aaron M. McCright and Terry Nichols Clark.
Includes bibliographical references.
Description based on print version record.
Keywords: Human ecology; Human beings -- Effect of environment on; Nature -- Effect of human beings on; Ecological engineering; Social impact of environmental issues; Social Science -- Sociology -- General